Facioscapulohumeral Muscular Dystrophy - Knox, Renatta N (Continuum (Minneapolis, Minn.), 2025)
Facioscapulohumeral muscular dystrophy (FSHD) is one of the most common forms of muscular dystrophy, affecting individuals across the lifespan with variable severity. This article provides an overview of the distinctive genetic mechanisms underlying FSHD, its clinical manifestations, including pediatric-specific features, treatment, and the evolving landscape of clinical trials targeting disease-modifying therapies. FSHD arises from derepression of the transcription factor DUX4, which is toxic to skeletal muscle. This misexpression leads to a characteristic and progressive pattern of muscle weakness involving the facial, shoulder girdle, upper extremity, trunk, and leg muscles. Extramuscular manifestations, such as pain and fatigue, are frequently reported. Children with a severe, early-onset phenotype experience higher rates of extramuscular features, including hearing loss, cognitive impairment, and spinal deformities. Advances in the understanding of as the causative gene, combined with innovations in gene therapy, gene editing, small-molecule development, and drug delivery, have catalyzed the initiation of several clinical trials focusing on disease-targeted treatments in the near future. FSHD is caused by toxic expression of and presents with progressive, often asymmetric muscle weakness and extramuscular manifestations in a subset of patients. Advances in genetic understanding and therapeutic development have led to clinical trials targeting . Although care remains supportive, the field is entering an era of promising disease-modifying strategies.